Navigating Conflict: The Impact of Sudan Civil War on China's Energy Security Strategies (2023-2025) - Azyumardi Mumtazul Umam (Institute of International Studies, 2025)
This study examines China’s strategic response to the disruption of its energy interests following the outbreak of Sudan’s civil war in 2023. As a key African partner in China’s external energy portfolio, Sudan’s instability posed direct risks to Chinese state-owned enterprises (SOEs) such as CNPC and Sinopec. Employing a qualitative single-case study and grounded in Neorealism and Resource Dependence Theory (RDT), the research analyzes China's adaptive strategies using triangulated documentary data and NVivo-assisted thematic coding. Three core responses are identified: diversification of energy sources, informal political engagement with Sudanese actors, and technical-institutional adaptation by SOEs. Findings reveal a hybrid strategic posture in which China balances its non-interventionist doctrine with pragmatic adjustments in conflict zones. SOEs emerge as semi-autonomous agents capable of navigating political fragmentation and operational uncertainty, demonstrating infrastructural relocation, security corridor formation, and decentralized decision-making. This paper contributes to international relations scholarship by highlighting how great powers manage resource dependency amid geopolitical volatility. It challenges conventional assumptions about the rigidity of China’s foreign policy, showing its evolving flexibility under fragmented state conditions. The study recommends comparative research across other conflict-affected regions to test the generalizability of this adaptive model.